The effect of several factors on energy characteristics and burning rate of pyrotechnic compositions based on silic and trilead tetraoxide in some pyrotechnic devices - Nguyễn Văn Tính; Hoàng Trung Hữu; Hoàng Khắc Hoằng; Nguyễn Văn Hiếu (Journal of Military Science and Technology, 2022)
Pyrotechnic ignition is one of the important parts of the delay timing devices found in the fuses and rockets to provide operational reliability according to technical requirements. In this study, the burning rate and some energy characteristics of the pyrotechnic ignition were described. The research results showed that, pyrotechnic compositions containing 85.0% Pb3O4, 15.0% Si and 1.0% NC (over 100%) had a high and stable burning rate (109.0 mm/s) and good ignition ability.